MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK SISWA SEKOLAH DASAR: STUDI KONSEPTUAL - Lukman Saleh; Nizmah Amad Bahasoan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of technology-based learning media for elementary school students has become a crucial need in the digital era. Challenges faced by conventional learning, such as low motivation and difficulty understanding abstract concepts, drive the need for innovative teaching methods. This study aims to analyze the types of technology-based learning media that are effective in increasing elementary school students' motivation and understanding. The method used is descriptive qualitative through literature review and case studies. The results show that interactive multimedia, mobile applications, educational games, learning videos, and LMS contribute positively to learning motivation and conceptual understanding. Technology integration also supports the development of students' digital skills and creates more effective and engaging learning.